What is school-based management?. (World Bank, 2007)
School-based management (SBM) is the decentralization of authority from the central government to the school level. SBM has become a very popular movement over the past decade. The World Bank's work program emerged out of a need to define the concept more clearly, review the evidence, support impact assessments in various countries, and provide some initial feedback to teams preparing education projects. During the first phase of the SBM work program, the team undertook a detailed stocktaking of the existing literature on SBM. They also identified several examples of SBM reforms that they are now supporting through ongoing impact assessments. This report defines school-based management, presents its typology, describes a conceptual framework for analyzing SBM, and examines how SBM can increase participation and improve school outcomes